A modern housing solution for 700 million families in developing countries - Davis, Mohd Peter; Yahaya, Nurizan; Sabri, Bukryman; Ibrahim Bajunid, Anniz Fazli; Chou, Kan Yin; Ghazali, Mazlin (Elsevier, 2012)
This paper describes 12 years of research at Universiti Putra Malaysia in collaboration with a practicing architect and a building material entrepreneur. Honeycomb is a town planning concept of interlocking cul-de-sac courtyards. A novel survey was developed to evaluate the consumer acceptance of Honeycomb houses. Honeycomb was preferred by 94% of 1385 respondents in 5 housing surveys across peninsular Malaysia, compared to 6% for equivalent conventional housing. 54% of that preference was ‘passionate’ about Honeycomb housing compared to only 3% for conventional housing. Honeycomb housing shows great promise as an example for under developed cities across the world.